Development of an optimal protocol for molecular profiling of tumor cells in pleural effusions at single‐cell level. Issue 5 (2nd April 2021) - Nakamura, Ikuko Takeda; Ikegami, Masachika; Hasegawa, Nobuhiko; Hayashi, Takuo; Ueno, Toshihide; Kawazu, Masahito; Yagishita, Shigehiro; Goto, Yasushi; Shinno, Yuki; Kojima, Yuki; Takamochi, Kazuya; Takahashi, Fumiyuki; et al.
Abstract: Liquid biopsy analyzes the current status of primary tumors and their metastatic regions. We aimed to develop an optimized protocol for single‐cell sequencing of floating tumor cells (FTCs) in pleural effusion as a laboratory test. FTCs were enriched using a negative selection of white blood cells by a magnetic‐activated cell sorting system, and CD45‐negative and cytokeratin‐positive selection using a microfluidic cell separation system with a dielectrophoretic array. The enriched tumor cells were subjected to whole‐genome amplification (WGA) followed by genome sequencing. The FTC analysis detected an EGFR exon 19 deletion in Case 1 (12/19 cells, 63.2%), and EML4‐ALK fusion (17/20 cells, 85%) with an alectinib‐resistant mutation of ALK (p.G1202R) in Case 2. To eliminate WGA‐associated errors and increase the uniformity of the WGA product, the protocol was revised to sequence multiple single FTCs individually. An analytical pipeline, accurate single‐cell mutation detector (ASMD), was developed to identify somatic mutations of FTCs. The large numbers of WGA‐associated errors were cleaned up, and the somatic mutations detected in FTCs by ASMD were concordant with those found in tissue specimens. This protocol is applicable to circulating tumor cells analysis of peripheral blood and expands the possibility of utilizing molecular profiling of cancers. Abstract : An optimized protocol is established for single‐cell sequencing of floating tumor cells (FTCs) in pleural effusion as a laboratory test that could be utilized for patient care. The FTC analysis detected an EGFR exon 19 deletion in Case 1 (12/19 cells, 63.2%) and EML4‐ALK fusion in Case 2 (17/20 cells, 85%). A novel analytical pipeline, accurate single‐cell mutation detector (ASMD), was developed to identify somatic mutations in single cells accurately.